Implementasi Guru Kreatif dan Berkarakter melalui Pembelajaran Aktif, Inovatif, Kreatif, Efektif dan Menyenangkan (PAIKEM) Di Sekolah Menengah Kejuruan (SMK) Assalaam Sukoharjo Tahun Ajaran 2016/2017 - Saputra, Didin, Dr. Muthoifin, M.Ag, Dr. Mutohharun Jinan, M.Ag (2017)
The purpose of this research is to know about: (1) How are the implementation of creative and character teachers profile through active learning, innovative, creative and fun (PAIKEM) at the Vocational Secondary School (SMK) Assalaam Sukoharjo school year 2016/2017? (2) what are the driving approach a barrier factors of PAIKEM implementation in SMK Assalaam Sukoharjo school year 2016/2017? This research used descriptive qualitative approach. The object of this research are The Principal, The Teachers, Students and The Environment. Engineering data collection done by the observation method, interview and documentation. Technique of data analysis using model data collection and presentation of data, data reduction, withdrawal and verification conclusion. Based on the results of this research, it can be concluded that: (1) The Process of teaching and learning in SMK Assalaam can be said already implemented PAIKEM, it is visible from: The Activities of teachers, teaching and learning in SMK Assalaam apply various ways, methods and techniques in an effort to improve and develop the potential of the talent and interests of students. The Teachers maximize its ability to encourage students to self help in solving problems and expressing his ideas. About The activity of students, individual students engage actively in the process of teaching and learning. Liveliness and The Creativity of students is seen from how often they ask what is not yet fully understood, questioned the ideas of others and expressing his own. About The learning environment, an environment in SMK Assalaam created and are designed as best and as attractive as possible to foster students interest in learnin. (2) As for the factors that drive PAIKEM in SMK Assalaam school year 2016/2017: The Teachers who are competent in their field, a fellow teacher who support each other for the Betterment of education, students who have an interest and talent in their fields, and advice and adequate infrastructure. (3) where as the factors that inhibit the less time is: quite in the teaching and learning process because in solving problems takes a different and searching for the source of problems for students. Keywords: implementation; Creative teachers; the teacher character; PAIKEM